2021
DOI: 10.1111/jocd.14617
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of botulinum toxin type A for postoperative scar prevention and wound healing improvement: A systematic review and meta‐analysis

Abstract: Postoperative wound healing is permanently of great concern to both surgeons and patients because pathological scars, including hypertrophic scars and keloids, profoundly affect an individual's physical and psychological well-being by causing pruritus, ulceration, pain, and contractures. Normal scar formation is an overlapping and orderly process involving hemostasis, inflammation, proliferation, and remodeling phases. 1 Although the pathogenesis of abnormal scar formation remains obscure, it is believed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 84 publications
0
6
0
6
Order By: Relevance
“…Robotic-assisted or laparoscopic single-port surgery is wildly applied in various adult subspecialty [ 3 6 ]. And robotic-assisted single-port surgery is successfully used in pediatric pyeloplasty and cholecystectomy [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robotic-assisted or laparoscopic single-port surgery is wildly applied in various adult subspecialty [ 3 6 ]. And robotic-assisted single-port surgery is successfully used in pediatric pyeloplasty and cholecystectomy [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Operative data were recorded, including surgical site, whole operative time (skin to skin), trocar insertion time, Ureteral reimplantation time, blood loss, transfusions, and volumes. Postoperative and follow-up data were collected, including duration of fasting, duration of JJ tube and gastric tube use, duration of the ureteral catheter, postoperative SFU, change of pre-postoperative SFU, postoperative DRF, change of pre-postoperative DRF, postoperative APDRPU, change of pre-postoperative APDRPU, length of hospital stay, complications (urine leakage, infection, anastomotic stenosis), parents’ satisfaction scores to the surgical scar (Stony Brook Scar Evaluation Scale, SBSES) [ 3 ], and outcomes (3 months after surgery).…”
Section: Methodsmentioning
confidence: 99%
“…Some preliminary research suggests that BTXA may influence scar formation by reducing fibroblast proliferation, decreasing TGF expression, and altering collagen deposition and remodeling processes 20,21 . Many reviews and meta‐analyses have been conducted to support the effectiveness of BTXA in scar treatment 22–24 . Guo et al 25 concluded that BTXA injection can improve general scar quality and wound healing in the face and neck in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Many reviews and meta-analyses have been conducted to support the effectiveness of BTXA in scar treatment. [22][23][24] Guo et al 25 concluded that BTXA injection can improve general scar quality and wound healing in the face and neck in Asians. However, different anatomical locations have various propensities to scar formation, and orbicularis oris derives from eight muscle components with their origins in the modiolus at each angle of the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Of the four serotypes that infect humans, botulinum neurotoxin A (BoNT/A1) is the most potent followed by serotypes B (BoNT/B), E (BoNT/E) and F (BoNT/F) 11 . Notwithstanding the lethality of this agent, BoNTs are widely exploited in the medical domain to treat a broad range of neurological disorders as well as in the field of cosmetics [12][13][14] BoNTs are composed of two domains comprising a 50 kDa light chain (LC) and a 100 kDa heavy chain (HC). The LC is the catalytic domain of BoNTs.…”
Section: Introductionmentioning
confidence: 99%